2015
DOI: 10.1111/hex.12433
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer screening: what do long‐term smokers know and believe?

Abstract: ObjectiveTo explore knowledge and beliefs of long‐term smokers about lung cancer, associated risk factors and lung cancer screening.DesignQualitative study theoretically framed by the expanded Health Belief Model based on four focus group discussions. Content analysis was performed to identify themes of knowledge and beliefs about lung cancer, associated risk factors and lung cancer screening among long‐term smokers' who had and had not been screened for lung cancer.MethodsTwenty‐six long‐term smokers were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
128
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(154 citation statements)
references
References 22 publications
13
128
1
Order By: Relevance
“…Patient-provider discussions and subsequent healthcare provider recommendations are associated with increased cancer screening behavior in other types of cancer such as breast and colorectal with patient-provider discussions occurring in approximately 50 to 80% of screening eligible patients [15-17]. However, unlike many cancers, there is a higher level of stigma associated with lung cancer [18,19], which may be contributing to the overall low prevalence of patient-provider discussions in lung cancer screening. Smokers are a unique population different from those targeted for other types of cancer screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-provider discussions and subsequent healthcare provider recommendations are associated with increased cancer screening behavior in other types of cancer such as breast and colorectal with patient-provider discussions occurring in approximately 50 to 80% of screening eligible patients [15-17]. However, unlike many cancers, there is a higher level of stigma associated with lung cancer [18,19], which may be contributing to the overall low prevalence of patient-provider discussions in lung cancer screening. Smokers are a unique population different from those targeted for other types of cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Smokers are a unique population different from those targeted for other types of cancer screening. Smokers experience stigma, battle an addiction to nicotine, and perceive blame from others related to the perceived self-infliction of tobacco-related diseases secondary to lifestyle choices [18,19]. Therefore, perceived stigma seems relevant in lung cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…11 Another recent qualitative survey study of smokers reported that knowledge of the existence of LCS was low and that patient barriers to screening included inconvenience, stigma associated with smoking as a reason to avoid screening, and distrust of the healthcare system. 12 Even less is known about physician barriers to LCS. Possible physician barriers to LCS include a lack of awareness regarding guidelines for LCS, lack of time to counsel patients regarding LCS, or misperceptions regarding the risks and benefits of LCS.…”
mentioning
confidence: 99%
“…Smokers experience stigma, battle an addiction to nicotine, and perceive blame from others related to the perceived self-infliction of tobacco-related diseases secondary to their lifestyle choice, and in turn, individual health beliefs related to cancer screening may be influenced by an individuals’ smoking status. Based on our preliminary qualitative work, variables such as health beliefs (perceived risk, perceived benefits, perceived barriers, and self-efficacy) as well as perceived stigma, medical mistrust, cancer fatalism, fear, and worry seem to be uniquely relevant in lung cancer screening (Carter-Harris, Ceppa, Hanna, & Rawl, 2015). …”
mentioning
confidence: 99%